IRON PROFILE STATUS IN PSORIASIS PATIENTS AND THEIR CORRELATION WITH THE DEGREE OF SEVERITY OF DISEASE - RATHORE, SHEETAL; R JAIN, ANURADHA; KUMAR KAIN, MANISH; PANDYA, NITIN; SAXENA, TRIPTI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: (1) The objective of the study was to evaluate and compare the levels of ferritin, iron, total iron binding capacity (TIBC), and hemoglobin (Hb) in cases and controls (2) and to correlate these parameters with the severity of psoriasis. Methods: Iron-profile including serum ferritin, iron, TIBC, and Hb was evaluated in 100 subjects, 50 cases (psoriatic) and 50 controls (normal healthy individuals). A preformed pro forma was filled for each patient after taking written consent. Ferritin was evaluated using fully automated chemistry analyzer, iron, and TIBC were evaluated by semi-autoanalyzer and Hb by Automated Hematology Cell Counter. Results: In our study, a lower level of serum ferritin, iron, and Hb was found in cases than controls, whereas the levels of TIBC were found higher in cases than controls. (p<0.05) We found a negative correlation of ferritin and a positive correlation of hemoglobin with psoriasis area and severity index. Conclusion: We conclude that iron profile should be done early in the course of disease to improve dietary advices and treatment modalities.